Does Money Buy Higher Schooling? Evidence from Secondary School Track Choice in Germany - Marcus Tamm (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The German schooling system selects children into different secondary school tracks already at a very early stage in life. School track choice heavily influences choices and opportunities later in life. It has often been observed that secondary schooling achievements display a strong correlation with parental income. We use sibling fixed effects models and information on a natural experiment in order to analyze whether this correlation is due to a causal effect of income or due to unobservable factors that themselves might be correlated across generations. Our main findings suggest that income has no positive causal effect on school choice and that differences between high- and low-income households are driven by unobserved heterogeneity, e.g. differences in motivation or preferences.
Keywords: D31; I21; J13; 330; Child poverty; educational attainment; secondary schools; sibling differences; natural experiment